Investigation on resonant laser ablation spectrum of Fe in 281.5–285.5 nm wavelength region - Jing, Ma; Xuehan, Ji; Zhifeng, Cui (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Laser ablation of solid Ti samples has been studied using a tunable pulsed dye laser. Six resonant laser ablation (RLA) spectral lines of Fe in the Ti sample are firstly measured in the 281.5–285.5 nm wavelength region. The initial state of the RLA spectral lines is a5F, the resonant states are z5H0, x5P0 and y5G0, respectively. The influence of laser power density on the intensities of RLA spectrum is discussed. The relationship between the laser wavelength and the photo-ionization cross sections of the resonant state 5G0 is analyzed.
Optica Applicata, Vol. 38, 2008, nr 2, s. 405-411
Keywords: optyka; resonant laser ablation (RLA); resonant state; photo-ionization cross section